Spotlight on Isl1: A Key Player in Cardiovascular Development and Diseases - Ren, Jie; Miao, Danxiu; Li, Yanshu; Gao, Rui (Frontiers in Cell and Developmental Biology, 2021)
Cardiac transcription factors orchestrate a regulatory network controlling cardiovascular development. Isl1, a LIM-homeodomain transcription factor, acts as a key player in multiple organs during embryonic development. Its crucial roles in cardiovascular development have been elucidated by extensive studies, especially as a marker gene for the second heart field progenitors. Here, we summarize the roles of Isl1 in cardiovascular development and function, and outline its cellular and molecular modes of action, thus providing insights for the molecular basis of cardiovascular diseases.